2013
DOI: 10.9775/kvfd.2013.9072
|View full text |Cite
|
Sign up to set email alerts
|

Sığırlarda Babesia bovis ve Babesia bigemina’nın Reverse Line Blotting, Nested PCR ve Real Time PCR Teknikleri İle Karşılaştırmalı Tanısı

Abstract: SummaryThis study was carried out to compare Reverse Line Blotting (RLB), Nested PCR and Real Time PCR techniques in the molecular diagnosis of Babesia bovis and Babesia bigemina in cattle. Genomic DNA extractions were performed on 400 blood samples which were previously collected from cattle in various provinces of Turkey and stored in the laboratory with respect to use in different project studies. The concentrations of the DNAs were measured in NanoDrop spectrophotometer and analyzed by RLB, Nested PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…and Babesia spp.) and 10 species specific probes (T. annulata, T. buffeli, B. bigemina, B. bovis, B. divergens, B. major, A. centrale, A. marginale, A. bovis and A. phagocytophilum) were used in RLB ( There are many molecular-based studies aimed at detecting the presence and prevalence of theilerioisis, babesiosis, anaplasmois in cattle and ixodid ticks from Turkey (Aktas et., 2011;Altay et al, 2008a;2014;Ica et al, 2007a;2007b;Yildirim et al, 2013). However, there is not any molecular-based research on tick-borne parasites in cattle in Sivas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Babesia spp.) and 10 species specific probes (T. annulata, T. buffeli, B. bigemina, B. bovis, B. divergens, B. major, A. centrale, A. marginale, A. bovis and A. phagocytophilum) were used in RLB ( There are many molecular-based studies aimed at detecting the presence and prevalence of theilerioisis, babesiosis, anaplasmois in cattle and ixodid ticks from Turkey (Aktas et., 2011;Altay et al, 2008a;2014;Ica et al, 2007a;2007b;Yildirim et al, 2013). However, there is not any molecular-based research on tick-borne parasites in cattle in Sivas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two new isolates, one of which was in Babesia genus and the other in Anaplasma genus, were found in the region. There are molecular-based studies showing the presence of new tick-borne parasite isolates in Turkey (Altay et al, 2008a;Ica et al, 2007b There are many molecular-based studies aimed at detecting the presence and prevalence of theilerioisis, babesiosis, anaplasmois in cattle and ixodid ticks from Turkey (Aktas et., 2011;Altay et al, 2008a;2014;Ica et al, 2007a;2007b;Yildirim et al, 2013). However, there is not any molecular-based research on tick-borne parasites in cattle in Sivas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, serological studies based on Indirect Fluorescent Antibody Technique (IFAT) revealed exposure to B. bovis , B. bigemina , and B. divergens parasites in different regions of Turkey [ 108 , 109 , 110 ]. Molecular techniques, such as PCR and RLB, have been recently used to investigate the presence of bovine babesiosis in the country [ 100 , 111 , 112 ]. Combined serology and molecular results have shown that bovine babesiosis caused by B. bovis , B. bigemina , B. divergens , B. major , and B. occultans is widespread in several areas of Turkey ( Table 2 and Figure 1 ).…”
Section: Current Status Of Bovine Babesiosis In Turkeymentioning
confidence: 99%